The AMINO experiment: a laboratory for astrochemistry and astrobiology on the EXPOSE-R facility of the International Space Station. Issue 1 (January 2015) - Cottin, H.; Saiagh, K.; Guan, Y.Y.; Cloix, M.; Khalaf, D.; Macari, F.; Jérome, M.; Polienor, J.-M.; Bénilan, Y.; Coll, P.; Fray, N.; Gazeau, M.-C.; et al.
Abstract The study of the evolution of organic matter subjected to space conditions, and more specifically to Solar photons in the vacuum ultraviolet range (120–200 nm) has been undertaken in low-Earth orbit since the 1990s, and implemented on various space platforms. This paper describes a photochemistry experiment called AMINO, conducted during 22 months between 2009 and 2011 on the EXPOSE-R ESA facility, outside the International Space Station. Samples with relevance to astrobiology (connected to comets, carbonaceous meteorites and micrometeorites, the atmosphere of Titan and RNA world hypothesis) have been selected and exposed to space environment. They have been analysed after return to the Earth. This paper is not discussing the results of the experiment, but rather gives a general overview of the project, the details of the hardware used, its configuration and recent developments to enable long-duration exposure of gaseous samples in tight closed cells enabling for the first time to derive quantitative results from gaseous phase samples exposed in space.